Pengembangan Aplikasi Mobile Pembelajaran Pecahan dengan Integrasi 3D dan Bank Soal Dinamis - Mutyarsih Aghata Erviansah; Linda Fujiyanti; Indah Riezky Pratiwi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Technological developments in education have opened up opportunities to introduce more interactive learning media, particularly in mathematics lessons in elementary schools, which are still dominated by lecture-style teaching methods. Students' limited understanding of fractions highlights the need for alternative media that can present the material visually and in an easy-to-understand manner. Based on these needs, this study developed a mobile learning application for fractions that integrates learning videos, 3D visualization based on Augmented Reality (AR), and a dynamic question bank. The development was carried out using the Multimedia Development Life Cycle (MDLC) method through six stages, namely concept, design, material collecting, assembly, testing, and distribution. The application was tested on 15 fifth-grade students and a mathematics teacher to assess its feasibility, ease of use, material suitability, and interface display. The test results showed that the application was considered feasible and helped students understand the fraction material more concretely, especially through the 3D visualization and instructional video features. In addition, students responded positively to the application's flow and the variety of randomly presented exercises. Thus, this application can be an innovative learning medium that supports the mathematics learning process in elementary schools.